Henoch-Schönlein purpura in children from western Turkey: a retrospective analysis of 430 cases - Anil, Murat; Aksu, Nejat; Kara, Orhan Deniz; Bal, Alkan; Anil, Ayşe Berna; Yavaşcan, Onder; Un, Binnur (The Turkish Journal of Pediatrics, 2009)
The medical records of children discharged with a diagnosis of Henoch-Schönlein purpura (HSP) between January 1996 and March 2006 were analyzed retrospectively. The patient population consisted of 430 children (225 boys, mean age: 7.9 +/- 2.9 years; range: 2-14 years). At onset, purpura was present in all cases, arthritis/arthralgias in 195 (45.3%), abdominal involvement in 148 (34.4%), and renal involvement in 192 (44.7%). Purpura manifested after 24 hours of admittance in 64 patients (14.9%) (atypical cases). Multivariate analysis showed that female sex, atypical presentation and early corticosteroid treatment increased the risk of renal involvement (p